Faktor-faktor yang Mempengaruhi Kelancaran Produksi ASI pada Ibu Menyusui di Desa Bendan, Kecamatan Banyudono, Kabupaten Boyolali - Safitri, Indah, Anisa Catur Wijayanti, SKM., M.Epid, Kusuma Estu Werdani, SKM., M.Kes (2016)
A mother often have problems in exclusive breastfeeding, one of the main obstacles that milk production isn't smooth. Scope of exclusive breastfeeding in Central Java in 2012 (25.6%) lower than in 2011 (45.18%). This study aims to know the factors that affect lactation in Bendan Village, Banyudono District, Boyolali City. This research is an observational with cross sectional design. The population in this research are all mothers giving birth in Bendan Village, Banyudono District, Boyolali City in 2015. Amount of samples involve 50 people, with a sampling technique using total sampling. The bivariate analysis using Chi-Square and Fisher Exact Test. The results of the bivariate analysis show that there is no impact between the implementation of early initiation of breastfeeding (p = 0,474), there was no impact of breast care (p = 0,001), there is a impact between contraceptive use (p = 0,022), and there is a impact between existence of passive smoking (p = 0,010) with lactation in Bendan Village, Banyudono District, Boyolali City.